2016
DOI: 10.1007/s13277-016-5415-1
|View full text |Cite
|
Sign up to set email alerts
|

MiR-203 promotes the growth and migration of ovarian cancer cells by enhancing glycolytic pathway

Abstract: MicroRNAs (miRNAs) play an important role in the tumorigenesis of ovarian cancer. Previously, we have reported the dysregulation of miR-203 in the ovarian cancer tissues. However, the biological functions and molecular mechanisms of miR-203 in ovarian cancer remain unknown. Here, we showed that the expression of miR-203 was increased in ovarian cancer tissues compared with the adjacent non-cancerous tissues and the transcription of miR-203 was inhibited by P53. Forced expression of miR-203 in ovarian cancer pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(28 citation statements)
references
References 26 publications
0
28
0
Order By: Relevance
“…Zhao et al . have discovered that overexpressing PDH protein could abolish the oncogenic effects of miR-203, including promoting the metastasis of ovarian cancer cells in vivo and shortening the survival of the tumor-bearing nude mice [58]. Taken together, these studies suggest that a high PDH level correlates with a favorable prognosis and a prolonged survival of ovarian cancer patients.…”
Section: Discussionmentioning
confidence: 99%
“…Zhao et al . have discovered that overexpressing PDH protein could abolish the oncogenic effects of miR-203, including promoting the metastasis of ovarian cancer cells in vivo and shortening the survival of the tumor-bearing nude mice [58]. Taken together, these studies suggest that a high PDH level correlates with a favorable prognosis and a prolonged survival of ovarian cancer patients.…”
Section: Discussionmentioning
confidence: 99%
“…In the literature, there are contradicting results concerning miR-203 with some studies supporting a tumor promoting and others a tumor suppressive role. 37,38 However, it has also been suggested that miR-203 has a suppressing role on epithelialmesenchymal transition, by interfering with the TGFb-SMAD3 pathway. 39 In our study, miR-203 expression showed no consistent correlation with ZEB1 or ZEB2 expression, suggesting that it may affect epithelial-mesenchymal transition independently of ZEB1/ZEB2.…”
Section: Discussionmentioning
confidence: 99%
“…miRNAs play important roles in cancer by acting as tumor suppressors or oncogenes (25)(26)(27). Many aberrantly expressed miRNAs have been reported in EOC and involved in EOC cell proliferation, invasion, migration, metastasis and apoptosis (13,28,29). Therefore, miRNAs may be investigated as diagnostic and prognostic molecular biomarkers and therapeutic targets for patients with EOC.…”
Section: Discussionmentioning
confidence: 99%